[quotation] Wife of a husband - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Wife of a husband'His snoresprotect the sleeping hutbut the day sloadand the morrow sburdenweighs heavily overthe stooping mother as shesweeps the hutbolts the pentidies the hearthburies the red charcoalsand finally seeksher restless bedHis...